Objective responses to first-line neoadjuvant carboplatin–paclitaxel regimens for ovarian, fallopian tube, or primary peritoneal carcinoma (ICON8): post-hoc exploratory analysis of a randomised, phase 3 trial. Issue 2 (February 2021) - Morgan, Robert D; McNeish, Iain A; Cook, Adrian D; James, Elizabeth C; Lord, Rosemary; Dark, Graham; Glasspool, Rosalind M; Krell, Jonathan; Parkinson, Christine; Poole, Christopher J; Hall, Marcia; Gallardo-Rincón, Dolores; et al.
Summary: Background: Platinum-based neoadjuvant chemotherapy followed by delayed primary surgery (DPS) is an established strategy for women with newly diagnosed, advanced-stage epithelial ovarian cancer. Although this therapeutic approach has been validated in randomised, phase 3 trials, evaluation of response to neoadjuvant chemotherapy using Response Evaluation Criteria in Solid Tumors, version 1.1 (RECIST), and cancer antigen 125 (CA125) has not been reported. We describe RECIST and Gynecologic Cancer InterGroup (GCIG) CA125 responses in patients receiving platinum-based neoadjuvant chemotherapy followed by DPS in the ICON8 trial. Methods: ICON8 was an international, multicentre, randomised, phase 3 trial done across 117 hospitals in the UK, Australia, New Zealand, Mexico, South Korea, and Ireland. The trial included women aged 18 years or older with an Eastern Cooperative Oncology Group performance status of 0–2, life expectancy of more than 12 weeks, and newly diagnosed International Federation of Gynecology and Obstetrics (FIGO; 1988) stage IC–IIA high-grade serous, clear cell, or any poorly differentiated or grade 3 histological subtype, or any FIGO (1988) stage IIB–IV epithelial cancer of the ovary, fallopian tube, or primary peritoneum. Patients were randomly assigned (1:1:1) to receive intravenous carboplatin (area under the curve [AUC]5 or AUC6) and intravenous paclitaxel (175 mg/m 2 by body surface area) on day 1 of every 21-day cycle (control group; group 1); intravenous carboplatin (AUC5 or AUC6) on day 1 and intravenous dose-fractionated paclitaxel (80 mg/m 2 by body surface area) on days 1, 8, and 15 of every 21-day cycle (group 2); or intravenous dose-fractionated carboplatin (AUC2) and intravenous dose-fractionated paclitaxel (80 mg/m 2 by body surface area) on days 1, 8, and 15 of every 21-day cycle (group 3). The maximum number of cycles of chemotherapy permitted was six. Randomisation was done with a minimisation method, and patients were stratified according to GCIG group, disease stage, and timing and outcome of cytoreductive surgery. Patients and clinicians were not masked to group allocation. The scheduling of surgery and use of neoadjuvant chemotherapy were determined by local multidisciplinary case review. In this post-hoc exploratory analysis of ICON8, progression-free survival was analysed using the landmark method and defined as the time interval between the date of pre-surgical planning radiological tumour assessment to the date of investigator-assessed clinical or radiological progression or death, whichever occurred first. This definition is different from the intention-to-treat primary progression-free survival analysis of ICON8, which defined progression-free survival as the time from randomisation to the date of first clinical or radiological progression or death, whichever occurred first. We also compared the extent of surgical cytoreduction with RECIST and GCIG CA125 responses. This post-hoc exploratory analysis includes only women recruited to ICON8 who were planned for neoadjuvant chemotherapy followed by DPS and had RECIST and/or GCIG CA125-evaluable disease. ICON8 is closed for enrolment and follow-up, and registered with ClinicalTrials.gov, NCT01654146 . Findings: Between June 6, 2011, and Nov 28, 2014, 1566 women were enrolled in ICON8, of whom 779 (50%) were planned for neoadjuvant chemotherapy followed by DPS. Median follow-up was 29·5 months (IQR 15·6–54·3) for the neoadjuvant chemotherapy followed by DPS population. Of 564 women who had RECIST-evaluable disease at trial entry, 348 (62%) had a complete or partial response. Of 727 women who were evaluable by GCIG CA125 criteria at the time of diagnosis, 610 (84%) had a CA125 response. Median progression-free survival was 14·4 months (95% CI 9·2–28·0; 297 events) for patients with a RECIST complete or partial response and 13·3 months (8·1–20·1; 171 events) for those with RECIST stable disease. Median progression-free survival for women with a GCIG CA125 response was 13·8 months (95% CI 8·8–23·4; 544 events) and 9·7 months (5·8–14·5; 111 events) for those without a GCIG CA125 response. Complete cytoreduction (R0) was achieved in 187 (56%) of 335 women with a RECIST complete or partial response and 73 (42%) of 172 women with RECIST stable disease. Complete cytoreduction was achieved in 290 (50%) of 576 women with a GCIG CA125 response and 30 (30%) of 101 women without a GCIG CA125 response. Interpretation: The RECIST-defined radiological response rate was lower than that frequently quoted to patients in the clinic. RECIST and GCIG CA125 responses to neoadjuvant chemotherapy for epithelial ovarian cancer should not be used as individual predictive markers to stratify patients who are likely to benefit from DPS, but instead used in conjunction with the patient's clinical capacity to undergo cytoreductive surgery. A patient should not be denied surgery based solely on the lack of a RECIST or GCIG CA125 response. Funding: Cancer Research UK, UK Medical Research Council, Health Research Board in Ireland, Irish Cancer Society, and Cancer Australia.